Microbial- and thiosulfate-mediated dissolution of mercury sulfide minerals and transformation to gaseous mercury - Vázquez-Rodríguez, Adiari; Hansel, Colleen M.; Zhang, Tong; Lamborg, Carl; Santelli, Cara M.; Webb, Samuel; Brooks, Scott (Frontiers in Microbiology, 2015)
Mercury (Hg) is a toxic heavy metal that poses significant environmental and human health risks. Soils and sediments, where Hg can exist as the Hg sulfide mineral metacinnabar (β-HgS), represent major Hg reservoirs in aquatic environments. Metacinnabar has historically been considered a sink for Hg in all but severely acidic environments, and thus disregarded as a potential source of Hg back to aqueous or gaseous pools. Here, we conducted a combination of field and laboratory incubations to identify the potential for metacinnabar as a source of dissolved Hg within near neutral pH environments and the underpinning (a)biotic mechanisms at play. We show that the abundant and widespread sulfur-oxidizing bacteria of the genus Thiobacillus extensively colonized metacinnabar chips incubated within aerobic, near neutral pH creek sediments. Laboratory incubations of axenic Thiobacillus thioparus cultures led to the release of metacinnabar-hosted Hg(II) and subsequent volatilization to Hg(0). This dissolution and volatilization was greatly enhanced in the presence of thiosulfate, which served a dual role by enhancing HgS dissolution through Hg complexation and providing an additional metabolic substrate for Thiobacillus. These findings reveal a new coupled abiotic-biotic pathway for the transformation of metacinnabar-bound Hg(II) to Hg(0), while expanding the sulfide substrates available for neutrophilic chemosynthetic bacteria to Hg-laden sulfides. They also point to mineral-hosted Hg as an underappreciated source of gaseous elemental Hg to the environment.